A bistable vibration isolator with nonlinear electromagnetic shunt damping. (February 2020) - Yan, Bo; Ma, Hongye; Zhang, Lu; Zheng, Wenguang; Wang, Ke; Wu, Chuanyu
Highlights: We develop a bistable vibration isolator (BVI) with several permanent magnets. We propose the concept of nonlinear electromagnetic shunt damping (N-EMSD). The effect of negative resistance on isolation performance are investigated. N-EMSD can regulate the motion types of BVIs by changing negative resistance. The transmissibility of BVIs can be smaller than 1 in part of the resonance region. Abstract: This paper presents a bistable vibration isolator (BVI) with several ring permanent magnets (PMs) and utilizes nonlinear electromagnetic shunt damping (N-EMSD) to improve the vibration isolation performance of the BVI. The theoretical model of N-EMSD is established. The harmonic balance method (HBM) is employed to derive the transmissibility of the BVI with N-EMSD. The analytical, numerical and experimental efforts are performed to investigate the vibration isolation performance of the BVI with N-EMSD. The results demonstrate that when the BVI is in the interwell oscillation, two peaks appear in the transmissibility curve and the transmissibility could be smaller than 1 between the two peaks. With the increase of the negative resistance, the motion of the BVI changes from the aperiodic/chaotic interwell oscillation to intrawell oscillation, resulting in the increase of the isolation band and the improved vibration isolation performance. The effects of the nonlinear electromagnetic coupling coefficient and the negative resistance are also investigated. The BVI with N-EMSD provides a feasible approach to study the vibration isolation characteristic of bistable structures.